"Unstabile" feste Wortverbindungen: Zur Dynamik des phraseologischen Sprachbestandes - Stefaniya Ptashnyk (Hermes, 2005)
This article deals with the relationship between stability and variability within phraseology. The investigation focuses on phraseological modiﬁcations as occasional units, created for certain texts or communicative situations. They unfold their potential particularly on the level of text constitution as well as pragmatics. At the same time, modiﬁcations are also considered as an important means of phraseological derivation: Frequently occurring (common) modiﬁ cations may become usual and lexicalized in the language system. The investigation on the basis of newspaper examples has shown that such modiﬁcation mechanisms as development of the phraseological ﬁgure, substitution and reduction produce derivatives with an intensiﬁed afﬁnity for usualization.